Biochemical Markers of Cardiovascular Diseases : Diagnostic and Prognostic Applications (Medical Forum Monthly, 2023)
Objective: The main objective of the study is to find the diagnostic and prognostic biochemical markers of cardiovascular disease.Study Design: A prospective cohort studyPlace and Duration of Study: This study was conducted at the Fazaia Ruth PFAU Medical College, Karachi from February 2023 till April 2023.Materials and Methods: The research followed a prospective cohort design, aiming to assess the association of specific biochemical markers with cardiovascular disease outcomes over the study period. A total of 500 participants were recruited for the study. Inclusion criteria included individuals aged 18 years and above with a confirmed diagnosis of cardiovascular disease, including coronary artery disease, heart failure, and atrial fibrillation. Patients with a history of previous cardiovascular events or interventions were also included. Exclusion criteria involved patients with acute infections, autoimmune diseases, or severe renal or hepatic impairment.Results: A total of 500 participants were recruited for the study, with an average age of 60 years (± 8.5 years). The study population consisted of 250 males (50%) and 250 females (50%), reflecting a balanced gender distribution. The baseline clinical assessment revealed that 300 participants (60%) had a diagnosis of coronary artery disease, 150 participants (30%) had heart failure, and 50 participants (10%) had atrial fibrillation. The mean systolic blood pressure was 130 mmHg (± 10 mmHg), and the mean diastolic blood pressure was 80 mmHg (± 8 mmHg).Conclusion: It is concluded that this study highlights the diagnostic and prognostic potential of cardiovascular biomarkers in risk assessment and patient management. The intervention led to favorable changes in biomarker levels, potentially reducing cardiovascular risk.